A Multicountry Study of the Violence-Related Risk Factors for Early Sexual Debut and Risky Sexual Behavior in Adolescents. Issue 3 (February 2022) - Smith, Lee; Jacob, Louis; López-Sánchez, Guillermo F.; Grabovac, Igor; Yang, Lin; Pizzol, Damiano; Sigman, Aric; McDermott, Daragh; Koyanagi, Ai
Globally, the prevalence of adolescent sexual intercourse and violence is high. However, to date, no study has investigated the association between violence and sexual behavior in a large representative sample of adolescents, while multicountry studies are also lacking. The objective was thus to examine the relationship between being physically attacked and physical fighting with sexual intercourse, multiple sexual partners, and non-condom use among adolescents aged 12 to 15 years from 43 low- and middle-income countries. Cross-sectional data from 127, 513 adolescents participating in the Global School-based Student Health Survey 2003–2016 were analyzed. Data on being physically attacked and physical fighting were assessed through self-report. Data on sexual behavior were collected as follows: (a) ever having had intercourse; among those who reported having had intercourse, (b) multiple (≥2) lifetime sexual partners, and (c) condom use in last sexual intercourse. Data were analyzed using multivariable logistic regression analysis with violence as the exposure and sexual behavior as the outcome, with odds ratios being estimated. Physical attack was dose-dependently and significantly associated with all three sexual behavior outcomes with it being associated with 1.42 (95% confidence interval [CI] = [1.16, 1.74]), 2.13 (95% CI = [1.39, 3.27]), and 1.48 (95% CI = [1.10, 2.00]) times higher odds for sexual intercourse, condom non-use, and multiple sex partners, respectively, when the highest category was compared with the lowest (i.e., ≥4 times vs. 0 times). As for physical fights, compared with not being in a fight in the past 12 months, being in a fight ≥4 times was associated with 2.34 (95% CI = [2.03, 2.70]) and 1.98 (95% CI = [1.56, 2.52]) times higher odds for sexual intercourse and multiple sex partners, respectively. In conclusion, in a large global sample of adolescents, physical attack and physical fight were associated with greater risk of engaging in sexual behavior. Multidimensional government programs and policies addressing violence in young adolescents may lead to reduction in early sexual debut and other risky sexual behavior.